Saudi female EFL learners’ task engagement: the role of agency and self-regulation - Hajar Khalifa Al Sultan (Institute of Advanced Engineering and Science, 2026)
Despite governmental reforms promoting independent learning, Saudi English as a foreign language (EFL) classrooms continue to use teacher-centered methods that limit learners’ autonomy and ability to self-regulate. This study uses a sociocultural framework and a qualitative design that includes semi-structured interviews and classroom observations of first-year Saudi female students enrolled in a university listening and speaking course. It aims to address the lack of qualitative evidence on how learner agency and self-regulation influence task engagement, and to examine how these factors affect student engagement in university-level language classrooms. Thematic analysis (TA) revealed that scaffolded autonomy and emotionally supportive classroom environments were especially influential in reducing anxiety and fostering confidence and independence. Findings show that engagement increases when students are offered structured opportunities to make choices, self-regulate, and learn in emotionally safe environments. Learners demonstrated agency through task choice, role negotiation, and alignment of assignments with personal preferences. Simultaneously, self-regulation was enacted through planning, emotional control, self-monitoring, and adaptive strategies such as peer observation and anxiety management. These findings illustrate that agency and self-regulation are socially constructed processes that flourish through interaction, guided support, and student-centered pedagogy. Addressing gaps in experimental research, the study presents how agency and self-regulation develop in real Saudi EFL classrooms